Hubungan Intensitas Penggunaan Media Gadget Dengan Speech Delay Pada Anak Balita Di Kelurahan Pannampu Kota Makassar - Nurfadliah Zamzani, Siti; Zelfia, Zelfia; Ahdan, Ahdan (UNIVERSITAS MUSLIM INDONESIA, 2022)
The purpose of this study was (1) to determine the relationship between the intensity of gadget media use and speech delay in children under five in the Pannampu sub-district, Makassar City. (2) To determine the level of speech delay in children under five aged 2-5 years in Pannampu Makassar Village. The method used in this study is a quantitative method. And this type of research is analytic observational with a cross sectional design. The population in this study were all children aged 2-5 years.. This research lasted for one month and was located in Pannampu village. Data collection techniques through the distribution of questionnaires and KPSP. The results of this study indicate that the intensity of gadget use on speech delays based on research from fifty respondents, most of whom are male, namely 34 people with a percentage of 68%, and based on age the highest is 25 people at the age of 4-5 years with a percentage 50%, and based on the intensity of the use of gadgets on speech delay in toddlers where there are 28% of toddlers who experience speech delay under study, this is from the results of the chi square test analysis obtained that the value of p = 0.000 < value a = 0.05 which means that there is a relationship between the intensity of media use gadgets against speech delay in toddlers.